Positive views on antipsychotic long-acting injections: results of a survey of community patients prescribed antipsychotics - Shubhra Mace; Oscar Chak; Sharanjeet Punny; Daniel Sedough-Abbasian; Chirag Vegad; David M. Taylor (SAGE Publishing, 2019)
Background: We aimed to assess patients' views about antipsychotic long-acting injections (LAIs). Methods: We interviewed patients prescribed an antipsychotic (oral or LAI) in our community teams. In a subanalysis, responses were analysed for differences between patients currently receiving an LAI and those prescribed only oral medication. Results: In total, 226 patients (57%) completed the study questionnaire. The majority agreed that LAIs ensured delivery of the right amount of medication and protection against hospital admissions (57% and 60%, respectively). A minority of participants were more concerned than not about the use of a needle (46%), pain from injection (48%) and the need to travel to receive the injection (34%). A majority expressed a preference for injection site (deltoid or gluteal) (65%) and clinic location (69%). A higher proportion of patients currently receiving an LAI compared with those prescribed oral medication thought an LAI was beneficial because this formulation obviated the need to: swallow tablets (63% versus 41%; p  = 0.0013), remember to take tablets daily (75% versus 51%; p  = 0.0004), remember tablets when away from home (72% versus 49%; p  = 0008). Current LAI users were more likely than those on oral treatment to agree that LAIs keep patients out of hospital (76% versus 44%; p  = 0.0001) and that the injection ensured delivery of the right amount of medication (71% versus 44%; p  = 0.0002). Women were more likely than men to prefer administration by a clinician of the same gender (34% versus 12%; p  = 0.0001). Conclusions: In our study, a greater proportion of patients prescribed an LAI regarded LAIs as beneficial compared with those on oral medication.